Heart Rate Reactivity, Neighborhood Disadvantage, and Antisocial Behavior - Portnoy, Jill (Crime & delinquency, 2020)
This article examines whether heart rate stress reactivity interacts with neighborhood disadvantage to predict antisocial behavior. Antisocial behavior was assessed in a community sample of 445 males and females (Mage = 11.92 years), using respondent and parent measures of antisocial behavior. Heart rate stress reactivity interacted with neighborhood disadvantage to predict parent-reported antisocial behavior. Specifically, the relationship between neighborhood disadvantage and antisocial behavior was stronger among children with lower heart rate reactivity. This study is the first to find that heart rate stress reactivity interacts with the neighborhood environment to predict antisocial behavior. Findings demonstrate the importance of examining biological factors in conjunction with the broader environmental context to understand the development of antisocial behavior.